2011
DOI: 10.1002/jwmg.134
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fences for containing feral swine under simulated depopulation conditions

Abstract: Populations of feral swine (Sus scrofa) are estimated to include >2 million animals in the state of Texas, USA, alone. Feral swine damage to property, crops, and livestock exceeds $50 million annually. These figures do not include the increased risks and costs associated with the potential for feral swine to spread disease to domestic livestock. Thus, effective bio‐security measures will be needed to quickly isolate affected feral swine populations during disease outbreaks. We evaluated enclosures built of 0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…Several reports have examined the efficacy of a variety of psychological, physical and biological barrier alternatives to traditional methods to evaluate their potential to be used for excluding or containing wild ungulates. Frightening devices , laser lights (VerCauteren et al, 2006a), propane gas exploders (Gilsdorf et al, 2004), livestock protection dogs (VerCauteren et al, 2008;Gehring et al, 2011), human-used bump gates (VerCauteren et al, 2009), electrified enclosures (Karhu and Anderson, 2006;Reidy et al, 2008) and fencing (VerCauteren et al, 2006b;Lavelle et al, 2011;Phillips et al, 2012) have all been evaluated and have varying efficacy in deterring wild ungulates from cattle resources. A fence design has been tested to successfully exclude elk without impeding other wildlife, including smaller ungulates , which is based on the fact that different body size impacts the ability to breach.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have examined the efficacy of a variety of psychological, physical and biological barrier alternatives to traditional methods to evaluate their potential to be used for excluding or containing wild ungulates. Frightening devices , laser lights (VerCauteren et al, 2006a), propane gas exploders (Gilsdorf et al, 2004), livestock protection dogs (VerCauteren et al, 2008;Gehring et al, 2011), human-used bump gates (VerCauteren et al, 2009), electrified enclosures (Karhu and Anderson, 2006;Reidy et al, 2008) and fencing (VerCauteren et al, 2006b;Lavelle et al, 2011;Phillips et al, 2012) have all been evaluated and have varying efficacy in deterring wild ungulates from cattle resources. A fence design has been tested to successfully exclude elk without impeding other wildlife, including smaller ungulates , which is based on the fact that different body size impacts the ability to breach.…”
Section: Introductionmentioning
confidence: 99%
“…Fencing has been proposed for containment of emergency disease epidemics in free-ranging feral swine (Lavelle et al, 2011); however pathogen containment will likely not occur with fences alone, because of their high construction costs, incomplete effectiveness, and because they are time consuming to erect (Reidy et al, 2008;Lavelle et al, 2011). For example, in Australia it has been demonstrated that several weeks could be expected to pass before passive surveillance detected an emergency epidemic in feral swine (Hone and Pech, 1990); during this time there could be substantial spread of pathogens and related disease.…”
Section: Introductionmentioning
confidence: 99%
“…While field trials have produced fence designs that will contain pigs (Lavelle et al 2011), Hone and Atkinson (1983) found that pigs can breach many types of fences and learn where they are most easily breached. Previous studies found that wild pigs tend to access fields closest to a wildland edge (Geisser and Reyer 2004;Thurfjell et al 2009).…”
Section: Tejon Ranch Conservancymentioning
confidence: 99%
“…If in good repair, the perimeter fences would be considered pig-proof based on small-scale fence trials (Hone and Atkinson 1983;Lavelle et al 2011): They were approximately 3.2 to 3.6 feet (0.9 to 1.1 meters) tall and made of 2.5-inch (6.4-centimeter) mesh chain link with horizontal barbed wire strands. Single or double strands of barbed wire typically extended above the top of the chain link.…”
Section: Two Fenced Farms Assessedmentioning
confidence: 99%